Role of leptin as a biomarker for early detection of renal cell carcinoma? No evidence from a systematic review and meta-analysis - Perumal, Komathi; Huin, Weng Kit; Yap, Ning Yi; Ong, Teng Aik; Gobe, Glenda Carolyn; Rajandram, Retnagowri (Elsevier, 2019)
Renal cell carcinoma (RCC) is the commonest from of renal neoplasm. Although surgery is a successful curative treatment for localized RCC, most patients are diagnosed with advanced or metastatic RCC, which has poor prognosis. RCC is classified by stage and grade using tissue samples. Whilst these provide good prognostic information, they are not very useful for early detection. Proteins that are dysregulated in patient's serum can be a valuable alternative and less invasive biomarker for early detection of the disease. For this reason, a hypothesis was formed that leptin is a possible biomarker for early detection and prognostication of RCC. The literature has disparate results on the usefulness of leptin as a biomarker for the early detection of RCC. Hence, a systematic review and a meta-analysis was carried out to investigate whether serum leptin could be a reliable diagnostic and prognostic factor in RCC patients. Literature on the available cohort and case-control studies on serum leptin in RCC was searched in electronic databases and included to evaluate this adipokine in the progression of RCC. The relevant studies were evaluated for the diagnostic and prognostic value of leptin in RCC patients. Overall, only 6 original research studies matched selection criteria and were included for meta-analysis. This study was hypothesised that; leptin might be a useful biomarker for early detection and prognostication of RCC. However, the data were presented in this study did not support our hypothesis. Serum leptin levels in RCC patients do not strongly associate with the development or progression of RCC, thus cannot act as a biomarker for early detection in RCC in patients. Extending our hypothesis further to include levels of obesity and RCC development may be worthwhile, but studies are currently limited. © 2019 Elsevier Ltd